Diagnosis and Treatment of Angiography Positive Medium to Large Vessel Childhood Primary Angiitis of Central Nervous System (p-cPACNS): An International Survey - Angela S. Quan; Jürgen Brunner; Benjamin Rose; Martin Smitka; Gabriele Hahn; Clare E. Pain; Renate Häfner; Fabian Speth; Lucia Gerstl; Christian M. Hedrich; Christian M. Hedrich (Frontiers Media S.A., 2021)
Childhood Primary Angiitis of Central Nervous System (cPACNS) is rare, but can cause significant damage and result in disability or even death. Because of its rarity, the sometimes acute and variable presentation, limited awareness, and the absence of widely accepted diagnostic and therapeutic standards, cPACNS is a diagnostic and therapeutic challenge. Three subcategories of cPACNS exist, including angiography-positive non-progressive p-cPACNS, angiography-positive progressive p-cPACNS which both affects the medium to large vessels, and angiography-negative small vessel sv-cPACNS. Diagnosis and treatment of cPACNS relies on personal experience, expert opinion and case reports/case series. To collect information on diagnostic and therapeutic approaches to transient and progressive cPACNS, a survey was shared among international clinicians (German Society for Pediatric Rheumatology, the Pediatric Rheumatology European Society, the German speaking "Network Pediatric Stroke," and members of the American College of Rheumatology/CARRA Pediatric Rheumatology list server). Results from this survey will be used to define statements toward a consensus process allowing harmonization of diagnostic and therapeutic approaches and the generation of evidence in a rare condition.